Meningoensefalitis Manifestation in Wegener’s Granulomatosis with Anca Negative: Case Report - Sudibyo, Triyanti Kurniasari Ananta Putri; Mulya, Deshinta Putri; Budiono, Eko; Satiti, Sekar; Rosalia, Levina Prima (Jurnal Penyakit Dalam Indonesia, 2019)
Wegener’s granulomatosis is a vasculitis that affects small to medium blood vessels, generally occurring at the age of 64- 75 years with an incidence of 8-10 / 1,000,000 people. Meningoencephalitis manifestations are rarely found in Wegener’s granulomatosis with the incidence only in the range of 0-7%. Anti-neutrophil cytoplasmic antibody (ANCA) is often used in diagnosing Wegener’s granulomatosis, but negative ANCA can be found in 10-20% of cases. A 30-year-old man came with a decrease in consciousness. His anamnesis and physical examination showed signs that led to Wegener’s granulomatosis, despite negative ANCA examination results. After getting therapy according to the management of the Wegener’s granulomatosis there is a clinical improvement in the patient. This case is raised because it is a rare case and needs sharpness in establishing a diagnosis. Wegener’s granulomatosis can cause very bad progress, but if handled properly, complete remission can be achieved.